Behaviors of dewaterability and heavy metals of waste activated sludge conditioned by heat-activated peroxymonosulfate oxidation - Huang, Zaichun; Liu, Changgeng; Zhu, Xuejun; Xiang, Guoqi; Zeng, Chenghua; Zhong, Yuquan (Chemical papers, 2020)
In this work, heat-activated peroxymonosulfate (heat-PMS) oxidation was used to condition waste activated sludge. The results showed that the optimal temperature and PMS dosage for sludge dewatering were 75 °C and 150 mg/g-volatile solids (VS), and the addition of rice husk (100–400 mg/g-VS) was favorable to further enhance sludge dewaterability. Under optimal conditions, the capillary suction time reduction and water content of sludge cake were 82.4% and 65.8%, respectively. The significant improvement of sludge dewaterability was ascribed to the releases of extracellular polymeric substances (EPS)-bound water and cell water caused by the significant breakdown of tightly bound EPS, as well as the skeleton effect. In addition, heat-PMS oxidation has been demonstrated with the merits of improving the immobilization of heavy metals (HMs) and weakening their environmental risk. After conditioning, HMs solubilization was enhanced significantly and their leaching toxicity decreased obviously. Meanwhile, HMs were transformed into more stable forms. Therefore, heat-PMS oxidation might be a potential and desirable technology for sludge conditioning with respect to the enhancement of sludge dewaterability and the decrease of HMs environmental risk.